Preparation and re-examination of Li4Ti4.85Al0.15O12 as anode material of lithium-ion battery - Cai, R.; Yuan, T.; Ran, R.; Liu, X.; Shao, Zongping (2011)
Spinel-type Al3+-doped Li4Ti5O12 oxide with the nominal composition of Li4Ti4.85Al0.15O12 was synthesized by a cellulose-assisted glycine–nitrate combustion process at reduced temperatures. X-ray diffraction characterization demonstrated that all Al3+ was successfully incorporated into the spinel lattice structure after calcination at 700°C. The Al3+ doping did not have obvious effect on the phase formation and phase structure while it led to an increase in surface area and a decrease in crystallite size of the oxide. The discharge capacity, the rate performance and the cycling stability were all slightly improved after the Al3+ doping. First discharge capacity ∼221 mAh g−1 was achieved for the as-synthesized Li4Ti4.85Al0.15O12 from calcination at 700°C, higher than 189 mAh g−1 for the pristine Li4Ti5O12 prepared by the same way. Al3+ was likely incorporated into both Li+ tetrahedral site and Ti4+ octahedral site with the majority into the Ti4+ site. Al3+ doping into the Li+ tetrahedral site increased the reducibility of Ti4+; consequently comparable electronic conductivity was observed for Li4Ti5O12 and Li4Ti4.85Al0.15O12 after the reduction. However, it also induced a decrease of lithium-ion diffusion coefficient and a transition of rate-limiting step of the electrode reaction from electron charge transfer for Li4Ti5O12 to Li+ diffusion for Li4Ti4.85Al0.15O12. The improved performance from the Al3+ doping was mainly attributed to the increased surface area of the oxide.